Numerical computation of compressible flow in S-ducts and bifurcated ducts - Ng, Yin Kwee. (2008)
This paper describes the development and application of a numerical method for the stable implementation of a low-Reynolds-number (LRN) k-e model into an explicit finite-volume time-marching scheme.